A dose titration study into the effects of diazepam or midazolam on the propofol dose requirements for induction of general anaesthesia in client owned dogs, premedicated with methadone and acepromazine. (10th June 2013) - Robinson, Rebecca; Borer‐Weir, Kate
Abstract: Objective: To assess the effect of a benzodiazepine co‐induction on propofol dose requirement for induction of anaesthesia in healthy dogs, to describe any differences between midazolam and diazepam and to determine an optimal benzodiazepine dose for co‐induction. Study design: Prospective, randomised, blinded placebo controlled clinical trial. Animals: Ninety client owned dogs (ASA I‐III, median body mass 21.5kg (IQR 10‐33)) presented for anaesthesia for a variety of procedures. Methods: Dogs were randomised to receive saline 0.1 mL kg −1, midazolam or diazepam at 0.2, 0.3, 0.4 or 0.5 mg kg −1 . All dogs received 0.01 mg kg −1 acepromazine and 0.2 mg kg −1 methadone intravenously (IV). Fifteen minutes later, sedation was assessed and scored prior to anaesthetic induction. Propofol, 1 mg kg −1, was administered IV, followed by the treatment drug. Further propofol was administered until endotracheal intubation was possible. Recorded data included patient signalment, sedation score, propofol dosage and any adverse reactions. Results: Midazolam (all groups combined) significantly reduced propofol dose requirement compared to saline ( p < 0.001) and diazepam ( p = 0.008). Midazolam (0.4 mg kg −1 ) significantly reduced propofol dose requirement ( p = 0.014) compared to saline, however other doses failed to reach statistical significance. Diazepam did not significantly reduce propofol dose requirement compared to saline ( p = 0.089). Dogs weighing <5 kg, regardless of treatment group, required a greater propofol dose than those weighing 5–40 kg ( p = 0.002) and those >40 kg ( p = 0.008). Dogs which were profoundly sedated required less propofol than those which were mildly sedated ( p < 0.001) and adequately sedated ( p = 0.003). Conclusions and clinical relevance: Midazolam (0.4 mg kg −1 ) given IV after 1 mg kg −1 of propofol significantly reduced the further propofol dose required for intubation compared to saline. At the investigated doses, diazepam did not have significant propofol dose sparing effects.